Renal Artery Stenosis Treated Successfully With Shockwave Intravascular Lithotripsy - Lee, Danielle (JACC Case Rep, 2020)
Renal artery stenosis (RAS) typically involves varying degrees of calcification, and treatment can be fraught with risk and suboptimal results. Intravascular lithotripsy (IVL) uses shockwaves to fragment calcium to facilitate angioplasty. We present a case of severe bilateral RAS successfully treated with IVL and stenting after conventional methods had failed. (Level of Difficulty: Intermediate.)